Impact of soil and water conservation measures on soil degradation status of an agricultural watershed in Shivalik region - Bhattacharyya, P; Yadav, R P; Arya, S L; Aggarwal, R K; Tiwari, A K (The Indian Journal of Agricultural Sciences, 2008)
A study was conducted during 2000-04 to evaluate the impact of a soil conservation package including diversion drains for runoff and collection of rainwater in village water harvesting structures, crop diversification and improved production technologies on soil degradation in small agricultural watershed of Shivalik region. Two water harvesting structures were renovated to create a storage capacity of 2.4 ha-m. A drainage network including 800 m long brick lined drain increased catchment area of water harvesting structures from 2.5 to 8.5 ha. The conservation measures along with crop diversification and integrated nutrient management reduced the area weighed degradation index of the watershed from 2.11 to 1.29. The nutrient value index for P and K increased from 1.57 to 2.27 and 2.08 to 2.12, respectively because of P fixation and nutrient rich sediment deposition in low-lying undulating land. Nitrogen improvement was utilized far crop production. The annual net returns/ha increased from Rs 7 448 to 24 590 due to project implementation.